Living Qur`an di Media Sosial: Analisis Akun Instagram @Tadabburquranid - Farhan, Muhammad; Dalil, FItri Yeni M (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this study is to identify the verses of the Qur'an written on the @Tadabburquranid Instagram account and to explain how the form of classification of the verses of the Qur'an written on the @Tadabburquranid Instagram account. This research is a qualitative research using descriptive method. The results of this study indicate that: (1) The Living Qur'an phenomenon has undergone a significant transformation in the digital era, especially through the use of Qur'anic verses on social media such as Instagram. In 2019 the Instagram account @Tadabburquranid has uploaded 23 posts containing verses of the Qur'an consisting of 21 surahs and 29 verses, which means that one post can contain more than one surah and one verse. (2) The verses posted on the @Tadabburquranid account can be classified based on the outlines of the content of the Qur'an according to the thoughts of Yasir and Jamaruddin, namely: faith (Tawhid), teachings about worship, laws and regulations, wa`ad and wa`id, stories in the Qur'an and the basis of science.